Interventions to improve gender equity in eye care in low-middle income countries: A systematic review. (4th May 2019) - Mercer, Gareth D.; Lyons, Penny; Bassett, Ken
ABSTRACT: Purpose : Women bear an inequitable burden of blinding conditions compared to men primarily because they have more limited access to eye care services. This systematic review sought evidence regarding interventions to increase gender equity in eye care. Methods : We searched MEDLINE, Cochrane Central Register of Controlled Trials, EMBASE, and EBSCO CINAHL, and contacted experts to identify studies in low- and middle-income countries of health services interventions for age-related cataract, childhood cataract, and trachoma. Eligible studies could be clinical trials or observational studies, but had to present sufficient data for intervention effects to be estimated separately for women and men. Results : We included four cluster RCTs and nine observational studies. All were judged to have serious risk of bias. Six studies examined interventions involving training rural community volunteers to identify, educate and assist individuals with unmet eye care needs. Interventions were associated with reduced gender inequities in all-cause blindness, clinic attendance, cataract surgery coverage and trachoma treatment coverage (low-to-very low quality evidence). Studies in Nepal and Tanzania examining a multicomponent intervention to improve follow-up after pediatric cataract surgery found reduced gender inequities in follow-up rates at 10 weeks (low quality evidence). Conclusion : Limited evidence exists to inform health service planners regarding interventions to reduce gender inequity in visual impairment and blindness. Training community volunteers to identify and counsel affected individuals, and empower them to circumvent or challenge socioeconomic barriers to accessing care holds promise. Future interventions ought to explicitly consider gender in their design and implementation, and incorporate high-quality evaluation efforts.